Forestry Sector-its Contribution to Gross National Product - Pant, M. M. (Indian Forester, 1977)
In computing GNP, ironically enough, the present system by and large evaluates dead forest resources and the dynamic aspects of forestry and its innumerable services are completely lost through inadequate understanding and unsatisfactory evaluation system. There are numerous statistical gap in the present compntation system. The quantity of forest products and their prices are being grossly underestimated. The sawn output is grossly under-reported because of the existence of a paraliel black market economy. The actual production of firewood alone is likely to exceed 3 to 4 times the reported figure. Some important forestry outputs such as food and fibre crops produced through agri-silvicultural practices, wild life capital growth and its its value, and others given in Appendix IIB, are presently Ignored. The value of the elemental services generated by the Forestry Sector are presently being ignored quantifiable services like grasing, lopping, fishing and hunting, etc., are not being objectively accounted for, to indicate contribution towards the GNP. Certain conceptual difficulties exist in quantifying various intangible services of the Forestry Sector. Till such time, therefore, as acceptable evaluation methods are worked out a complementry approach of evaluating the impalpable services directly from the cost of providing these may be adopted. The value added in the processing of wood and forestry products for tile manufacture of the final finished products is accruing entirely to the manufacturing sector. The forest service should claim its legitimate share (wages, salaries, profit, etc.) out of the value added in the production processes. This will necessitate some rethinking of the National Industrial Classification, 1970, and may need dialogues particularly with the Central Statistical Organisation. Some suggestions for filling up certain statistical gaps existing at present in the systems have been made. The need for amending the international standardised classification as a step for more pragmatic system for the preparation of the National Accounts has also been discussed.